Isolation and optimization of IAA producing Burkholderia seminalis and its effect on seedlings of tomato - Padmavathi Tallapragada; Rashmi Dikshit; Swetha Seshagiri (Songklanakarin Journal of Science and Technology (SJST), 2015)
The present study was carried out to isolate Plant Growth Promoting Rhizobacteria (PGPR) strain from rhizosphere. Isolated strain was identified as Burkholderia seminalis using 16s rDNA. This strain was subjected to screening for indole acetic acid (IAA) production followed by optimization using statistical approach namely response surface methodology. IAA production from B. seminalis in nutrient broth supplemented with tryptophan was confirmed through thin layer chromatography (TLC). The effect of cell free culture medium (CFCM) obtained from isolated strain was examined on tomato seeds with Murashige and Skoog 2 (MS2) medium and it had a positive impact on germination of seeds. Further the IAA produced by B. seminalis in nutrient broth was purified and different concentrations were checked on tomato seed. It was observed that the germination index was similar to the control but the lateral roots development increased in the presence of 1 and 3 mg/mL of IAA in the medium.